Post-Quantum Cryptography Review in Future Cybersecurity Strengthening Efforts - Mu'min, Muhammad Amirul; Safitri, Yana; Saputra, Sabarudin; Sulistianingsih, Nani; Ragimova, Nazila; Abdullayev, Vugar (Scientific Journal of Engineering Research, 2025)
The development of quantum computing technology brings significant challenges to conventional crypto-graphic systems that are currently widely used in digital data security. Attacks made possible by quan-tum computers have the potential to weaken classical algorithms such as RSA and ECC, so a new ap-proach is needed that can guarantee long-term security. This study aims to systematically review the ef-fectiveness and readiness of the implementation of post-quantum cryptography (PQC) algorithms, espe-cially those that have been recommended by NIST, in order to strengthen the resilience of future cyberse-curity systems. The method used was a structured literature study with comparative analysis of lattice-based (Kyber and Dilithium), code-based (BIKE), and hash-based (SPHINCS+) PQC algorithms. Data are obtained from official documents of standards institutions as well as the latest scientific publications. The results of the analysis show that lattice-based algorithms offer an optimal combination of security and efficiency, and demonstrate high readiness to be implemented on limited devices. Compared to other al-gorithms, Kyber and Dilithium have advantages in terms of performance and scalability. Thus, this re-search contributes in the form of mapping the practical readiness of the PQC algorithm that has not been widely studied in previous studies, and can be the basis for the formulation of future cryptographic adop-tion policies. These findings are expected to help the transition process towards cryptographic systems that are resilient to quantum threats.